Syntheses, characterisations and electrochemical studies of nickel(II) and cobalt(II)-lIgand assisted cooperative complexes / Jeevithra Dewi Subramaniam - Jeevithra Dewi , Subramaniam (2020)
A newly designed tetradentate ligand L1 (L1 = 3,6-bis(pyrazol-1-yl)-pyridazine) which offers multinucleation sites on its moiety structure has been prepared. The reaction of L1 with different molar ratio of nickel and cobalt salts lead to the formation of di- and tetranuclear complexes [NiII 2(L1)2(CH3CN)4](PF6)4 (1), [NiII 4(L1)4(μ-OH)4](ClO4)4 (2) and [CoII/III(L1)4(μ-CH3O)2(μ-O)2](PF6)3(NO3) (3), which served as the attempt to design of catalysts based on cheap and earth-abundant metals for carbon dioxide reduction. The presence of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as the base controls the nuclearity of the complex formation. In the absence of DBU, complex 1 was formed in dinuclear fashion whereas complex 2 and 3 formed tetranuclear fashion in the presence of DBU. The three complexes were structurally characterised by elemental analysis, nuclear magnetic resonance spectroscopy (NMR), Fourier transform infrared analysis (FT-IR), X-ray diffraction analysis, and voltammetry studies. Crystal structures revealed all complexes are centrosymmetric and adopted slightly distorted octahedral geometry. Complex 1 crystallises in monoclinic C2/c space group as the Ni(II) centre is octahedrally bound to L1 in a trans-isomer arrangement. Complex 2 crystallises in tetragonal I41/amd space group with four L1 and four hydroxy bridging ligands linked to Ni(II) centre in cisisomer arrangement. Complex 3 crystallises in orthorhombic Cmm space group with four L1, two methoxy bridging ligand and two oxo bridging ligands linked to Co(II/III) centre in cis-isomer arrangement. FTIR confirmed the L1 and bridging ligands were bound to the metal centre by exhibiting the shift at